Maulānā ʻUbaidullāh Sindhī : ḥālāt-i zindagī, taʻlīmāt aur siyāsī afkār - Sarvar, Muḥammad, 1906-1983 (SAMP early 20th-century Indian books project, 1943)
On the life of ʻUbaidullāh Sindhī, 1872-1944, Indian Muslim revolutionary.